Macular edema - Audo, Isabelle 1968- (Developments in ophthalmology / series editor F. Bandello, 2017)
Since the publication of the first edition of 'Macular Edema - A Practical Approach' in 2010, modern imaging related to the pathophysiology of macular edema has progressed immensely. In particular, optical coherence tomography (OCT) techniques and new approaches, including "en face" OCT and OCT angiography, have become essential methods. This second, revised and extended edition incorporates the latest developments. It includes discussions of OCT-A imaging for better differential diagnosis and for state-of-the-art imaging figures. It elaborates practice guidelines and treatment algorithms, and also explores the pathophysiological basis of macular edema in detail. It discusses novel and various applications of drug delivery to the posterior segment. The latest peer-reviewed clinical studies are deliberated and real-world data from clinical settings offer additional new insights. This volume is a practical and useful update for all retina specialists interested in keeping abreast with the rapidly changing developments in the diagnosis and treatment of macular edema.